Options to improve family income, labor input and soil organic matter balances by soil management and maize–livestock interactions. Exploration of farm-specific options for a region in Southwest Mexico. Issue 4 (August 2015) - Flores-Sánchez, Diego; Groot, Jeroen C.J.; Lantinga, Egbert A.; Kropff, Martin J.; Rossing, Walter A.H.
Abstract Farming systems in the Costa Chica region in Mexico face limitations linked to low yields and soil fertility degradation. Several alternative maize-based cropping systems have been proposed to improve current limitations. These field-level options need to be evaluated at farm level in order to assess their feasibility, taking into account input requirements, contributions to self-sufficiency in food and long-term soil fertility, and the availability of labor. In this study, we defined four scenarios to explore consequences of changes in current farming systems for eight typical farms in the region; the first two scenarios comprised redressing current imbalances in crop nutrition and organic matter (OM) supply, respectively, and the last two scenarios explored high fertilizer input and animal husbandry. Farms responded in different ways to the various options depending on available land, current soil quality, current cropping systems and presence of livestock. Improvements in crop nutrition based on mineral fertilizers increased family income but only had substantial effects on soil OM (SOM) balances when fertilizer rates were double the amount currently subsidized. Addition of organic fertilizers resulted in positive effects on SOM balance, but with often strong trade-offs with family income due to costs of acquisition, transport and application. Animals played an important role in increasing SOM balances, but had relatively little effect on improving family income. The results demonstrated that improvements in family income and SOM balance at farm scale were feasible but that without more fundamental system changes trade-offs between short-term yield increases and longer-term soil fertility increases should be expected. The results highlight the need for policies that take into account farm-specific differences in crop and livestock intensification opportunities.